Genetic Diversity and Host Immune Response of Trichomoniasis Among Women: Keanekaragaman Genetik dan Respons Imun Inang pada Trikomoniasis pada Wanita - Baraa Abdulsalam Hraija (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Trichomonas vaginalis is one of the most prevalent protozoan sexually transmitted infections affecting women and is associated with reproductive and inflammatory complications. Specific Background: Accurate molecular detection and characterization of the parasite are essential for understanding its epidemiology and its interaction with host immune responses. Knowledge Gap: Despite the widespread occurrence of trichomoniasis, limited molecular and immunological data are available regarding the genetic diversity of local isolates and their relationship with inflammatory biomarkers in Iraqi populations. Aims: This study investigated the prevalence of T. vaginalis infection among women in Wasit Province, Iraq, using PCR targeting the internal transcribed spacer 1 (ITS1) region, examined the phylogenetic relationships of detected isolates, and assessed associated immune markers including cysteinyl leukotrienes, interleukin-8, and leukotriene B4. Results: Molecular analysis identified a 7.56% infection rate among 291 examined women. Sequencing and phylogenetic analysis of 22 isolates revealed strong similarity with previously reported Iraqi strains. Infected women demonstrated significantly elevated levels of CysLTs, IL-8, and LTB4 compared with non-infected individuals. Novelty: The study integrates molecular detection, phylogenetic characterization, and immunological biomarker evaluation of T. vaginalis isolates in a single population-based investigation. Implications: These findings contribute to improved epidemiological understanding of trichomoniasis and highlight the potential role of inflammatory mediators in the pathophysiology of infection. Keywords: Trichomonas Vaginalis, ITS1 Region, Molecular Detection, Phylogenetic Analysis, Immune Biomarkers Key Findings Highlights PCR analysis identified trichomoniasis in 7.56% of examined women from Wasit Province. Sequenced isolates clustered with previously reported Iraqi strains in phylogenetic analysis. Infected participants showed marked elevation of inflammatory mediators including IL-8 and leukotrienes.